Four-dimensional bioprinting: Current developments and applications in bone tissue engineering. (1st January 2020) - Wan, Zhuqing; Zhang, Ping; Liu, Yunsong; Lv, Longwei; Zhou, Yongsheng
Abstract: Four-dimensional (4D) bioprinting, in which the concept of time is integrated with three-dimensional (3D) bioprinting as the fourth dimension, has currently emerged as the next-generation solution of tissue engineering as it presents the possibility of constructing complex, functional structures. 4D bioprinting can be used to fabricate dynamic 3D-patterned biological architectures that will change their shapes under various stimuli by employing stimuli-responsive materials. The functional transformation and maturation of printed cell-laden constructs over time are also regarded as 4D bioprinting, providing unprecedented potential for bone tissue engineering. The shape memory properties of printed structures cater to the need for personalized bone defect repair and the functional maturation procedures promote the osteogenic differentiation of stem cells. In this review, we introduce the application of different stimuli-responsive biomaterials in tissue engineering and a series of 4D bioprinting strategies based on functional transformation of printed structures. Furthermore, we discuss the application of 4D bioprinting in bone tissue engineering, as well as the current challenges and future perspectives. Statements of significance: In this review, we have demonstrated the 4D bioprinting technologies, which integrate the concept of time within the traditional 3D bioprinting technology as the fourth dimension and facilitate the fabrications of complex, functional biological architectures. These 4D bioprinting structures could go through shape or functional transformation over time via using different stimuli-responsive biomaterials and a series of 4D bioprinting strategies. Moreover, by summarizing potential applications of 4D bioprinting in the field of bone tissue engineering, these emerging technologies could fulfill unaddressed medical requirements. The further discussions about future challenges and perspectives will give us more inspirations about widespread applications of this emerging technology for tissue engineering in biomedical field. Graphical abstract: Image, graphical abstract